Enhancement of the lighting quality for white light-emitting diodes with CaSc2O4:Ce3+ phosphor - Phuc Dang Huu; Phung Ton That; Phan Xuan Le; Nguyen Le Thai (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
For the task of realizing greater progress for the light output in white light-emitting diodes (WLEDs), this study focuses on the luminescence temperature subordination feature of CaSc2O4:Ce3+ phosphor (abbreviated to CaS for this study). Some other aspects of the phosphor were also included in this piece of paper: Huang-Rhys coupling factor, Stokes shift, triggering power, abatement temperature and especially, abatement behavior in CaSc2O4:Ce3+. Creating the bluish-green LEDs by the combination of blue InGaN chip and CaSc2O4:Ce3+ is the primary purpose. CaSc2O4:Ce3+ appears to be a decent green phosphor that can be used in WLEDs made of blue InGaN chip. Production tasks may be based on our investigation for the task of making desirable WLED devices that meet the production demands.